Italy and Problem of Control over Dodecanese Islands in 1912-1914 - T. P. Nesterova (Научный диалог)
The history of diplomatic struggle of Italy for the recognition of Italian control over the Dodecanese Islands is examined. It is emphasized that the archipelago, captured by Italy during the Libyan war of 1911-1912, had strategic importance as a natural centre to establish spheres of influence in the Eastern Mediterranean. It is noted that Italy had not originally sought the inclusion of the archipelago in its own land, but quickly showed interest to establish its power over the Dodecanese Islands and refused to implement the international agreements providing the evacuation of the Italian occupying forces from the archipelago. The article proves that the difficult diplomatic struggle in which, along with Italy, Greece and Ottoman Empire, the great European powers - France, Britain, Germany, Austria-Hungary - took part, did not led to the return of the disputed Islands to the Ottoman Empire or to their transfer to Greece, demanding these Islands on the basis of ethnic principle. The author argues that the persistence, under various pretexts, the Italian occupation of the Islands was as a result of significant diplomatic victory of Italy and subsequently allowed them to be Italian possession.